Design and simulation of piezoelectric micropump for a constant flow rate - A., Syed Abdul Bari (2016)
A micropump is just like any other ordinary pumps except that it deals with fluids in extremely small dimensions. It works based on the concept of suction and decompression. The challenges faced in designing a piezoelectric micropump are to have a controlled flow rate as well as increasing the efficiency of the pump. The objective of this project is to design a piezoelectric micropump which aims in maintaining a constant consistent flow rate of a liquid of approximately few microlitres per minute by adjusting the voltage and frequency. Different piezoelectric materials were used and their flow rates were studied and PZT proved to be the optimum choice. The projected results display a laminar flow at the required flow rate for the liquid purification system over a period of time. The flow rate of the micropump will be controlled by the voltage and the frequency applied to the piezoelectric layer. The flow rate of this micropump was compared with the theoretical value to study the comparison between the simulated and theoretical results. The simulation for this piezoelectric micropump is done using Intellisuite software. There existed a variation of 7% between the theoretical flow rate and simulated results when a voltage of 20 volts were applied, mean while there existed a variation of 12% when a voltage of 100 volts were applied. This piezoelectric pump is made of PZT (piezoelectric layer), Silicon (Fluid chamber) and Aluminum (Metal contact layer). The flow rate recorded was approximately 0.22 micro liters per second when a voltage of 10 volts were applied at 10 Hz. In conclusion, this piezoelectric micropump was designed for biomedical purposes, hence the requirement of a constant flow rate over a period of time. Shape of diaphragm and channel were designed in order to increase the efficiency of the flow.